2021
DOI: 10.1007/s00415-021-10559-w
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome and predictors of long-term disease activity in natalizumab-treated patients with multiple sclerosis: real life data from the Austrian MS Treatment Registry

Abstract: Objectives To evaluate long-term effectiveness of natalizumab (NTZ) and to determine demographic, clinical, and radiological predictors regarding long-term disease activity (≥ 7 years) in a nationwide observational cohort, using data collected prospectively in a real-life setting. Materials and methods We analysed data from 230 patients from the Austrian Multiple Sclerosis Treatment Registry (AMSTR), who had started treatment with NTZ at any time since 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
(69 reference statements)
0
8
0
Order By: Relevance
“…The long-term studies (Boziki et al, 2021;Butzkueven et al, 2020a;Guger et al, 2021;Prosperini et al, 2017) confirm that natalizumab is a highly effective treatment option for PwMS. Risk stratification for PML and risk management strategies that include patient education and close monitoring have improved outcomes and reduced the number of natalizumab-associated PML incidences (Vivekanandan et al, 2021;Vukusic et al, 2020).…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…The long-term studies (Boziki et al, 2021;Butzkueven et al, 2020a;Guger et al, 2021;Prosperini et al, 2017) confirm that natalizumab is a highly effective treatment option for PwMS. Risk stratification for PML and risk management strategies that include patient education and close monitoring have improved outcomes and reduced the number of natalizumab-associated PML incidences (Vivekanandan et al, 2021;Vukusic et al, 2020).…”
Section: Discussionmentioning
confidence: 77%
“…When initiated early in the disease course, natalizumab was associated with fewer relapses and reduced disability worsening (Butzkueven et al, 2020a;Wiendl et al, 2021). The long-term effectiveness of natalizumab was also described in other real-world studies (Boziki et al, 2021;Davidescu et al, 2021;Efthimios et al, 2021;Guger et al, 2021;Horakova et al, 2020;Prosperini et al, 2017). Results from these studies indicate that, when administered long-term, natalizumab is effective and has an adequate safety profile, provided subjects are closely monitored.…”
Section: Long-term Efficacy and Safety Of Natalizumabmentioning
confidence: 85%
See 1 more Smart Citation
“…Long-term data of natalizumab effectiveness from the Austrian MS Treatment Registry show a stable disease course regarding relapse activity and disease progression under natalizumab treatment for more than 7 years, with older age at natalizumab start (> 35 years) being the only significant risk factor for disease progression over long-term [ 24 ].…”
Section: Natalizumabmentioning
confidence: 99%
“…After two pivotal phase 3 clinical studies (AFFIRM and SENTINEL), natalizumab was approved for relapsing-remitting MS (RRMS) in 2004 by the US Food and Drug Administration and in 2015 by the Korea Food and Drug Administration (4)(5)(6). Observational studies demonstrated the long-term effectiveness and well-established safety profile of natalizumab (7,8). However, the predominant concern with the use of natalizumab is its association with the development of progressive multifocal leukoencephalopathy (PML), a rare serious opportunistic infection caused by the John Cunningham virus (JCV), which can cause severe disability or even death.…”
Section: Introductionmentioning
confidence: 99%